SALJUQIYLAR DAVRI TARIXINI О‘RGANISHGA DOIR - Furqat Toshboyev, Usmonov Navruz JDPU magistranti (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In the article, the authors provided information about the history of the Oghuz tribes, the Cynic Turkmen and the Seljuk state. Moreover, as important political events of the 9th-12th centuries. Issues such as the entry of the Oghuz tribes into Movaraunnahr, their location in the Nurota oasis, their migration to the western lands, and the creation of the Seljuk state were covered.